Knockout of Tmem70 alters biogenesis of ATP synthase and leads to embryonal lethality in mice - Vrbacký, Marek; Kovalčíková, Jana; Chawengsaksophak, Kallayanee; Beck, Inken M; Mráček, Tomáš; Nůsková, Hana; Sedmera, David; Papoušek, František; Kolář, František; Sobol, Margarita; Hozák, Pavel; Sedlacek, Radislav; et al. (Human molecular genetics, 2016)
TMEM70, a 21-kDa protein localized in the inner mitochondrial membrane, has been shown to facilitate the biogenesis of mammalian F1Fo ATP synthase. Mutations of the TMEM70 gene represent the most frequent cause of isolated ATP synthase deficiency resulting in a severe mitochondrial disease presenting as neonatal encephalo-cardiomyopathy (OMIM 604273). To better understand the biological role of this factor, we generated Tmem70-deficient mice and found that the homozygous Tmem70-/- knockouts exhibited profound growth retardation and embryonic lethality at ∼9.5 days post coitum. Blue-Native electrophoresis demonstrated an isolated deficiency in fully assembled ATP synthase in the Tmem70-/- embryos (80% decrease) and a marked accumulation of F1 complexes indicative of impairment in ATP synthase biogenesis that was stalled at the early stage, following the formation of F1 oligomer. Consequently, a decrease in ADP-stimulated State 3 respiration, respiratory control ratio and ATP/ADP ratios, indicated compromised mitochondrial ATP production. Tmem70-/- embryos exhibited delayed development of the cardiovascular system and a disturbed heart mitochondrial ultrastructure, with concentric or irregular cristae structures. Tmem70+/- heterozygous mice were fully viable and displayed normal postnatal growth and development of the mitochondrial oxidative phosphorylation system. Nevertheless, they presented with mild deterioration of heart function. Our results demonstrated that Tmem70 knockout in the mouse results in embryonic lethality due to the lack of ATP synthase and impairment of mitochondrial energy provision. This is analogous to TMEM70 dysfunction in humans and verifies the crucial role of this factor in the biosynthesis and assembly of mammalian ATP synthase.
Keywords: mutace; myši knockoutované; Mice; mitochondriální membrány; Mitochondrial Membranes; mitochondriální nemoci; mitochondriální protonové ATPasy; Membrane Proteins; Mutation; Mitochondrial Proteins; těhotenství; myši; Female; Homozygote; Metabolism, Inborn Errors; kardiomyopatie; homozygot; Adenosine Triphosphate; Pregnancy; Oxidative Phosphorylation; oxidativní fosforylace; membránové proteiny; vrozené poruchy metabolismu; ženské pohlaví; zvířata; adenosintrifosfát; Mitochondrial Proton-Translocating ATPases; Mice, Knockout; mitochondriální proteiny; mitochondrie; Mitochondrial Diseases; Animals; Mitochondria; Cardiomyopathies